The effectiveness of the Tech program in the development of cognitive functions in children with autism - Benguettaf , Mohamed; Baitaoui , Djamila (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2021)
Through our research, we have attempted to study autism, which is one of the most important causes of imbalance in cognitive ability and more particularly in the inability to communicate and integrate with others, which can only be done through understanding and language; this has a negative impact on the life of people diagnosed with autism. Indeed, it is a real problem that requires treatment by therapeutic and educational programs to reduce the seriousness of these problems on the lives of people with autism. The latter represent our objective which is to know if the therapeutic program "Teacch" has a positive and effective impact on improving the level of oral comprehension and the vocabulary result of this category. The study was carried out on 5 autistic children, including 3 boys. 2 girls out of 53 children diagnosed with autism at Mohamed Boudiaf hospital in Medea who suffer from language and verbal comprehension problems and whose their ages range between 4 and 7 years. The results of this research have been interpreted in light of the theoretical framework and the results of previous studies, so that they indicate that there are statistically significant differences between the anterior and posterior measures of the level of linguistic communication and of listening comprehension in favor of distance measurement. All differences are significant at the 0.05 level which means that children's linguistic development and autistic understanding are characterized by significant improvement after the implementation of the program. We emphasize through the results the importance and the effectiveness of the "Teacch" therapeutic program to improve the level of oral communication and comprehension of autistic children.